2021
DOI: 10.1038/s41467-021-21113-7
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2 limits intestinal tuft and goblet cell numbers through GSK3β-mediated restriction of epithelial IL-33

Abstract: Dynamic regulation of intestinal cell differentiation is crucial for both homeostasis and the response to injury or inflammation. Sprouty2, an intracellular signaling regulator, controls pathways including PI3K and MAPKs that are implicated in differentiation and are dysregulated in inflammatory bowel disease. Here, we ask whether Sprouty2 controls secretory cell differentiation and the response to colitis. We report that colonic epithelial Sprouty2 deletion leads to expanded tuft and goblet cell populations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 79 publications
6
34
0
2
Order By: Relevance
“…With respect to colorectal cancer (CRC), we demonstrated, for the first time, upregulation of SPRY2 in CRC [13] and inflammatory bowel disease (IBD) [14] along with an oncogenic role of SPRY2 in CRC [15]. More recently, increased expression of SPRY2 in IBD was also confirmed by other investigators [16].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…With respect to colorectal cancer (CRC), we demonstrated, for the first time, upregulation of SPRY2 in CRC [13] and inflammatory bowel disease (IBD) [14] along with an oncogenic role of SPRY2 in CRC [15]. More recently, increased expression of SPRY2 in IBD was also confirmed by other investigators [16].…”
Section: Introductionsupporting
confidence: 61%
“…In addition, SPRY2 might serve as a potential biomarker with respect to anti-EGFR treatment response in colon cancers [54]. Furthermore, another recent study found that SPRY2 was increased in colon epithelial cells in patients with ulcerative colitis and Crohn's disease [16]. More importantly, they revealed the underlying mechanism using a SPRY2 KO mice model and found that in response to acute colitis, deletion/suppression of SPRY2 played a protective role in maintaining the integrity of the colon epithelium against inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…ILC2 attracts and activates T H 2 cells by producing the type 2 cytokines IL-4, IL-5, and IL-13 [7,34]. As a result, effector cytokines such as IL-13 promote tissue remodeling by modulating crypt stemness and stimulating goblet cell (GC) and tuft cell hyperplasia in order to facilitate pathogen clearance [34][35][36].…”
Section: Type 2 Innate Lymphoid Cells (Ilc2) In Ibdmentioning
confidence: 99%
“…The failure to regulate the IL-33-tuft cell axis may be associated with SPRY2 (Sprouty2, an intracellular signaling regulator). SPRY2 expression has been shown to be enhanced in both CD and UC patients, resulting in tuft cells and GC inhibition [ 35 ]. Collectively, different studies showing both pathogenic and protective roles of IL-33 suggest that IL-33 may be a double-edged sword.…”
Section: Epithelium-derived Type 2 Immunity Associated Cytokinesmentioning
confidence: 99%
“…In response to enteric parasites that colonize the small intestine, increased IL-13 production by immune cells induced stem cells to differentiate to the tuft and goblet cell types via IL-4Rα signaling in the small intestine [6,9,33], but not in the colon [6]. Interestingly, differentiation of colonic tuft cells was found to be ATOH-1 dependent [13,30,34] and colonic tuft cell hyperplasia is recorded in response to changes in the microbiome and during acute inflammation [25,35]. Such variation in the regulation of differentiation hints at the probability that small intestinal and colonic ETCs may perform different functions [30].…”
Section: Tuft Cell Lineage Subtypes and Basic Biologymentioning
confidence: 99%